Beckman Facilities, Fullerton, California - Brock, Daniel W.
Exterior view of Beckman Instruments' Fullerton plant. In 1954, Beckman's headquarters moved from Pasadena to Fullerton.
Keywords: Factories; Buildings; Beckman Instruments, Inc.